Examining the Responsibility of Broken Home Parents for the Rights of Children at Berkah Orphanage Palangka Raya - Rismanto, Ikbal Reza; Rachmadi, Rachmadi (Universitas Islam Negeri Sumatera Utara, 2025)
This study examines the tendency of broken-home parents to place their children in orphanages, impacting their fulfillment of parental responsibilities. The research focuses on: 1) How do parents at Berkah Orphanage in Palangka Raya fulfill the rights of broken-home children? 2) How is this responsibility viewed from the perspective of Islamic law? This research employs an empirical method and a sociological approach to law, utilizing observation, interviews, and documentation for data collection. Findings indicate that parents strive to meet the basic needs of their children, such as shelter, food, healthcare, and education, although much of this role is assumed by the orphanage. From the perspective of maqāshid sharī'ah, entrusting children to an orphanage is considered appropriate for the child’s welfare